Centrifugal Separation of Carbon Isotopes Using Carbon Tetrafluoride as Processing Gas. (December 2020) - Sun, Q; Jian, C; Zhou, M; Pei, G
Abstract: At present, the application of carbon isotope is becoming more and more extensive, especially in the field of medical testing, and the demand for 13 C in high abundance is fast increasing. Using carbon tetrafluoride (CF4 ) as separation medium, study on centrifugal separation of carbon isotopes was carried out. Single-centrifuge experiments were done based on modified domestic gas centrifuges. As a result, the separation factor and single-centrifuge separative power under different working conditions were obtained. Based on the results of single-centrifuge separation experiments, cascade calculation of the enrichment of 13 C isotope was conducted by ideal cascade. According to calculation results, through two cascade separations, 13 C isotope could be enriched from 30% to above 99% in abundance. The study laid a good basement for production of 13 C isotope in high abundance.